Impacting Factors of Dividend Policy in Indonesian Banking Sector - Kosasih, Dicky Mikhael; Aditya, Febiyana; Rachma, Nabila (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
ABSTRACT. Further research is needed on the implementation of dividend policy in emerging market.  This phenomenon exists as there is no “one-size-fits-all” dividend policy evaluation factor that is applicable in every business sector. This study explores firms’ specific factors with the variables of corporate governance, firm size, and firm profitability along with economical phenomenon factor with the variable of inflation towards dividend policy at once. The data documentation techniques is secondary data collection from The Indonesia Stock Exchange, Bank Indonesia, journals, articles, and scientific papers. The data collected was coded and analyzed using SPSS (Statistical Package for Social Sciences). The result shows that dividend policy is affected by both internal (firm-specific factor) and external (economical phenomenon) stimuli. However, it is deduced from the tests results that there is a stronger impact arise from the internal factor; in comparison to the otherwise.